Phytochemical profiling, heavy metals composition, in silico aphrodisiac potential, and ADMET study of Gardenia erubescens (Sciences of Phytochemistry, 2023)
This study aimed to explore the phytochemical profile, heavy metal composition, in silico aphrodisiac potential, and ADMET study of Gardenia erubescens due to its folkloric acclaimed aphrodisiac use. The phytochemicals were quantified gravimetrically while the identification of bioactive compounds was carried out using a combined Gas spectrophotometer-mass spectrophotometer (GC-MS). Heavy metals were quantified using an atomic absorption spectrophotometer while the aphrodisiac and ADMET studies were in silico. The result showed the presence of alkaloids (22.33% ±1.45), saponins (20.17% ±1.88), glycosides (0.55% ±0.03), and flavonoids (32.67% ±1.45), with the absence of steroids and terpenoids. GC-MS analysis identified 25 compounds with linoleic acid having the highest peak area (28.01%) next to palmitic acid (14.08%). Chromium, Cadmium, and Lead were present in concentrations of 0.145 ±0.03, 0.001 ±0.00, and 0.065 ±0.03 ppm respectively. Ethyl D-glucopyranoside had the least BA (-8) and Ki (1.35 µM) docked with human arginase II while Tyrosinol had the least BA (-6.2) and Ki (28.21 µM) docked with phosphodiesterase 5 though both were higher than Sildenafil citrate. All the top docked compounds were predicted to be neither substrates nor inhibitors of P-glycoproteins and cytochrome P450 enzymes without CNS permeability and hepatotoxicity. Conclusively, the present study supports the folkloric aphrodisiac application of Gardenia erubescens, and the heavy metals level was below the acceptable regulatory level, thus, might be safe for occasional use. Additionally, the identified compounds might be considered a novel source of therapeutics against erectile dysfunction.